The Effect of Profitability, Corporate Social Responsibility Disclosure, and Capital Intensity on Tax Avoidance - Edo, Rizki; Nengzih, Nengzih (Research Horizon, 2025)
Tax avoidance remains a persistent issue in Indonesia’s manufacturing sector, which plays a major role in national GDP yet remains vulnerable to regulatory loopholes. This study aims to analyze the effects of profitability, capital intensity, and Corporate Social Responsibility (CSR) on tax avoidance, while examining firm size as a moderating variable. Using purposive sampling, the research selected 30 manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2019–2023, yielding 150 firm-year observations. Secondary data were obtained from annual reports, and analysis was conducted using panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). The results reveal that profitability has a significant negative effect on tax avoidance, indicating that more profitable firms tend to comply with tax regulations to maintain legitimacy and reputation. In contrast, CSR and capital intensity show no significant influence, and firm size does not moderate any of these relationships. These findings suggest that financial performance plays a greater role than structural or disclosure factors in determining tax behavior. The study contributes to the literature by providing empirical evidence on the determinants of tax avoidance in Indonesia’s manufacturing sector and offers policy implications for tax authorities to strengthen oversight of low-profit firms vulnerable to aggressive tax planning.